Hebrew-French bible glossaries and the question of Jewish-French cultural exchange in the High Middle Ages - Liss, Hanna; Dörr, Stephen (Corpus Masoreticum working papers, 2022)
In medieval northern France, Old French (the langue d’oïl), both spoken and written, was the vernacular for the Christian and Jewish populations alike. Before the Jews were expelled from the region, the Jewish scholarly elite had been culturally integrated to such an extent that their commentaries on the Bible and Talmud were augmented with French words taken from various literary genres. These so-called le‘azim, which were written in Hebrew letters, were considered so relevant that they were collected in special glossaries. Six full or partial Hebrew-French Bible glossaries and two alphabetically structured Hebrew-French vocabularia have been passed down to us. This article discusses the state of research of the Hebrew-French glossaries from the perspective of both Romance and Jewish studies and addresses groundbreaking questions that have yet been barely touched